William Wycherley - Vernon, P. F. (Writers and Their Work Series., 1965)
In this 1965 study, P.F. Vernon studies the life and work of William Wycherley as a satirist, concluding that his appeal is especially strong to the modern playgoer, whom he sets laughing 'in the same critical spirit that he intended'.